TANTANGAN PENERAPAN SOCIAL RETURN ON INVESTMENT (SROI) DI INDONESIA STUDI KASUS PADA WILAYAH PESISIR - Fety Widianti Aptasari; Baiq Krisnina Maharani Putri; Khairul Mujahidi; Ely Windarti Hastuti (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2024)
Socio-economic inequality in Indonesia remains a serious problem, with most of the country's wealth controlled by a small minority of the population. Coastal communities, especially fishermen, face severe poverty, prompting various entities to implement economic empowerment programs. However, the effectiveness of these programs is often questioned, leading to the Social Return on Investment (SROI) method being used to measure the social, economic and environmental impacts of such investments. SROI offers a more comprehensive evaluation approach, but its application in Indonesia, especially in coastal areas, is still very limited. This study aims to analyze the challenges of applying SROI in Indonesia's coastal areas, with a focus on economic empowerment programs. These challenges come from program providers, such as corporations that focus on regulatory compliance, governments that are more output-oriented, and NGOs with limited resources. In addition, challenges also come from beneficiaries, including low levels of education, short-term orientation towards aid, and daily economic constraints. This research offers a contribution to the development of more effective and sustainable economic empowerment policies and strategies in Indonesia, in order to reduce socioeconomic inequality nationwide.